Antenatal Care And Severe Pre-Eclampsia In Kathmandu Valley - Manandhar, Bekha Laxmi; Chongstuvivatwong, V; Geater, A (Journal of Chitwan Medical College, 2014)
Severe preeclampsia/eclampsia is one of the common cause of maternal and perinatal morbidity and mortality. So the prevention of this severe preeclampsia may prevent these complications. This study was undertaken to assess the association between antenatal care and severe pre-eclampsia/eclampsia, also to examine the role of other risk factors for severe preeclampsia/eclampsia. A case study was conducted during May to Oct 1994 in Kathmandu valley. This study failed to demonstrate that ANC could reduce the risk of severe pre-eclampsia/eclampsia. The incidence rate of ANC visits in third trimester was significantly lower among cases than among controls. Risk independently increased in women with a history of previous PET (OR 6.9, 95% CI 1.0-48.9), history of abortion (OR 4.5, 95% CI 1.1-19.3), late menarche (OR 3.7, 95% CI 1.6-8.4) and primigravidity (OR 2.9, 95% CI 1.2-7.4). Use of modern contraceptive methods decreased the risk (OR 0.21, 95% CI 0.05-0.83). Risk was also higher among the middle-income group (OR 3.6, 95% CI 1.2-10.7), manual workers (OR 13.4, 95% CI 4.5-40.3) and non-Hindu women (OR 9.9, 95% CI 3.0-32.3). This study did not demonstrate that ANC could reduce the risk of severe pre-eclampsia/eclampsia. The history of previous PET, abortion, late menarche and primigravidity status each independently increased risk. Use of modern contraceptive methods decreased the risk. Risk was higher among the middle-income group manual workers and non-Hindu women. Journal of Chitwan Medical College 2013; 3(4); 43-47 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9554